Spin crossover-induced colossal positive and negative thermal expansion in a nanoporous coordination framework material. Issue 1 (December 2017) - Mullaney, Benjamin; Goux-Capes, Laurence; Price, David; Chastanet, Guillaume; Létard, Jean-François; Kepert, Cameron
Abstract External control over the mechanical function of materials is paramount in the development of nanoscale machines. Yet, exploiting changes in atomic behaviour to produce controlled scalable motion is a formidable challenge. Here, we present an ultra-flexible coordination framework material in which a cooperative electronic transition induces an extreme abrupt change in the crystal lattice conformation. This arises due to a change in the preferred coordination character of Fe(II) sites at different spin states, generating scissor-type flexing of the crystal lattice. Diluting the framework with transition-inactive Ni(II) sites disrupts long-range communication of spin state through the lattice, producing a more gradual transition and continuous lattice movement, thus generating colossal positive and negative linear thermal expansion behaviour, with coefficients of thermal expansion an order of magnitude greater than previously reported. This study has wider implications in the development of advanced responsive structures, demonstrating electronic control over mechanical motion. Controlling mechanical motions in solid state devices is highly desirable for the development of nanoscale machines. Here, Kepert and colleagues exploit an ultra-flexible coordination framework in which thermally-controlled Fe(II) spin transitions result in remarkable flexing of the crystal lattice.